Citrus Pest Quick Guide: California Red Scale (Aonidiella aurantii): ENY2092/IN1384, 11/2022 - Martini, X.; Price, J. (EDIS, 2022)
This factsheet gives the general public and citrus growers basic knowledge regarding the California red scale. Written by X. Martini and J. Price, and published by the UF/IFAS Entomology and Nematology Department, November 2022.